Corak Ikan Koi Sebagai Sumber Inspirasi Dalam Karya Seni Lukis - Agus Deddy Krisna Adi Saputra, I Putu; Supriyatini, Sri; Wirakesuma, I Nengah (CITA KARA : JURNAL PENCIPTAAN DAN PENGKAJIAN SENI MURNI, 2021)
The general purpose of this research and creation is to revive the author's love for fauna, especially koi fish. The variety of life in God's creation is very interesting to be used as an idea for creating art, one of which is the koi fish. The attraction of koi fish lies in the variety of patterns, colors, and movements that are captivating. Judging from its existence, koi fish have long been a part of human life, from the imperial era in China and Japan several centuries ago to the present. The beauty of koi fish is an attraction for humans to own, maintain, even as part of a lifestyle that can improve economic status and social status. For the writer's life, koi fish is one part of a hobby that since childhood, can bring fun and entertainment, calm the soul, as well as a source of inspiration in creating painting. These works of art can add to the richness of the repertoire of visual arts in Indonesia, in terms of the concepts, media, and techniques that are revealed. The method used in this research is the first observation or direct observation of the object under study, data collection through interviews, the internet, books, and data analysis. While the method of creation used is exploration, experimentation and creation of works. From these methods, six works were realized, including: 1. Tanco and the Japanese Flag, 2. Samurai Shiro, 3. Gosanke Worldwide, 4. Peace and Calm, 5. Victory, 6. The King of Ornamental Fish. In realizing a work, it is viewed from two aspects, namely ideoplastic aspects and physioplastic aspects. The benefit of this creation is that the public can appreciate this painting, both in terms of aesthetics and ethics.